The Principle of Justice in the Executorial Title of Court Decisions and Its Relevance to Strengthening the Integrity of Judges - Fausi, Achmad (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This research is motivated by the lack of clarity in laws and regulations in detailing the principles of justice intended by the executorial title of court decisions. Although the executorial title represents the judge's oath and embodies the accountability of the decision to society, the state, and God, judicial corruption involving judges still occurs. Consequently, the executorial title appears perfect on paper but has not fully cultivated a collective consciousness among judges as systemic integrity. This study employs normative juridical legal research with a legal analysis focused on the application of interpretation methods and legal principles, utilizing legislative, historical, and comparative approaches. The theoretical framework integrates the theory of justice and Imam Ash-Syatibi's Maqashid Al-Syariah theory. The study finds that the principle of justice in the executorial title of court decisions arises from correct and fair formal procedures. Materially, the judicial process involves stages of scrutinizing, qualifying, and constituting, utilizing the thematic induction method, Istiqra' ma'nawi, and the principle of synergy of evidence (mabda' tadofur adillah). This results in decisions that meet criteria for legal and moral accountability. The ethical principles contained in the executorial title include divinity, fair conduct, honesty, wisdom, independence, high integrity, responsibility, self-respect, discipline, humility, and professionalism. These principles are closely related to efforts to combat judicial corruption, as they not only embody the spirit of realizing justice through decisions but also serve as ethical values that build strong character in judges. Thus, in their professional roles, judges are expected to demonstrate superior integrity and remain free from corrupt practices.